Chad's cabinet of icy curiosities: Sharpening the interpretation of subglacial and ice marginal environments during the LPIA glaciation of the Ennedi Plateau - Ricarda Wohlschlägl (Department of Geology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Christoph Kettler (Department of Sedimentary Geology, Geosphere Austria); Daniel Paul Le Heron (Department of Geology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); András Zboray (Fliegel Jezerniczky Expeditions) (Sedimentary Geology, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:2040019 The abstract is available here: https://uscholar.univie.ac.at/o:2040019